Cluster Preface: Alkene Halofunctionalization - Johnston, Jeffrey N.; Rovis, Tomislav (Synlett, 2018)
Jeffrey N. Johnston is a 1992 graduate of Xavier University where he completed his B.S. Chemistry degree (Honors, summa cum laude). With summer research stints in medicinal, polymer, and inorganic pigment chemistry under his belt, he transitioned to synthetic organic chemistry at The Ohio State University where he worked with Leo Paquette for his graduate work (PhD 1997). He completed postdoctoral studies with David Evans at Harvard University (USA) and was supported by an NIH Postdoctoral Fellowship. His independent career began in 1999 at Indiana University, where he was promoted to Professor of Chemistry before moving to Vanderbilt University in 2006. He is currently a Stevenson Professor of Chemistry. The commitment of his students and postdoctoral scholars to the discovery and development of new reactions and reagents, particularly in enantioselective catalysis, have led to numerous honors, including the Cope Scholar Award, a Fellowship from the Japan Society for the Promotion of Science, a Swiss Chemical Society Lectureship, and an Eli Lilly Grantee Award. It was graduate student Mark Dobish's discovery of the chiral proton-catalyzed enantioselective iodolactonization reaction (J. Am Chem. Soc.2012, 134, 6068) that began his group's exploits of alkene halofunctionalization reactions for the good of chemical synthesis.Tomislav Rovis was born in Zagreb in former Yugoslavia but was largely raised in southern Ontario, Canada. He earned his PhD degree at the University of Toronto (Canada) in 1998 under the direction of Professor Mark Lautens. From 1998–2000, he was an NSERC Postdoctoral Fellow at Harvard University (USA) with Professor David A. Evans. In 2000, he began his independent career at Colorado State University and was promoted in 2005 to Associate Professor and in 2008 to Professor. His group’s accomplishments have been recognized by a number of awards including an Arthur C. Cope Scholar, an NSF CAREER Award, a Fellow of the American Association for the Advancement of Science and a Katritzky Young Investigator in Heterocyclic Chemistry. In 2016, he moved to Columbia University where he is currently Professor of Chemistry.